The Impact of ESG on Firm Value: Empirical Study on Indonesia and Singapore Companies - Meini, Zumratul; Setijaningsih, Herlin Tundjung (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Environmental, Social, and Governance (ESG) is a concept focusing on the sustainability of development, investment, and business activities based on three criteria: environment, social, and governance. The increasing demand for attention to ESG in sustainability issues raises the question of whether companies that have concerns about the environment, social, and governance can increase the value of their firms. The aim of this study is to obtain empirical evidence of how ESG performance influences firm value, especially in Indonesia and Singapore. This study builds on previous research by analyzing each ESG pillar and considering behavioral differences between industries and countries to provide more comprehensive empirical evidence. This study’s population is companies listed on the Indonesia and Singapore Stock Exchanges from 2015 to 2022. The sample obtained in this study used the purposive sampling method which produced 82 company samples. Hypothesis testing was carried out by implementing multiple regression analysis showing that ESG performance can increase the firm's value. Furthermore, the impact of ESG performance on firm value does not differ between industries. Still, it differs between countries where the influence of ESG performance on firm value is higher in Indonesia compared to Singapore. Keywords: ESG, Industry, Firm Value